Experimental Investigation of a Planar Antenna with Band Rejection Features for Ultra-Wide Band (UWB) Wireless Networks. (2nd June 2019) - Khan, Muhammad Irshad; Khattak, Muhammad Irfan; Witjaksono, Gunawan; Barki, Zaka Ullah; Ullah, Sadiq; Khan, Imran; Lee, Byung Moo
Abstract : The Federal Communication Commission (FCC) has authorized the use of unlicensed ultra-wide band (UWB) spectrum in the frequency range from 3.1 to 10.6 GHz for a variety of short-range applications, including wireless monitors and printers, camcorders, radar imaging, and personal area networks (PANS). However, the interference between coexisting narrowband channels and UWB signals that share the same spectrum should be avoided by designing UWB antennas with band notch characteristics. This work presents a printed monopole antenna (PMA) with slots of different shapes etched in the radiating element to obtain band rejection in the three coexisting communication bands, i.e., Worldwide Interoperability for Microwave Access (WiMAX), Wireless Local Area Network (WLAN), and International Telecommunication Union (ITU). A rectangular slot is etched to reject the WiMAX band (3.01-3.68 GHz), an upturned C slot stops the WLAN band (5.18-5.73 GHz) while an inverted-U slot halts the ITU frequency band (7.7-8.5 GHz). The proposed antenna occupies a volume of 32 x 30 x 1.6 mm 3 and it radiates efficiently (>90%) with a satisfactory gain (>1.95 dBi) in the unnotched UWB frequency range. The simulations are performed in High Frequency System Simulator (HFSS), while the measurements are conducted in antenna measurement facility and found in close agreement with the former.